1064 nm FT-Raman spectroscopy for investigations of plant cell walls and other biomass materials - Agarwal, Umesh P. (Frontiers in Plant Science, 2014)
Raman spectroscopy with its various special techniques and methods has been applied to study plant biomass for about 30 years. Such investigations have been performed at both macro- and micro-levels. However, with the availability of the Near-IR (1064 nm) FT-Raman instruments where, in most materials, successful fluorescence suppression can be achieved, the utility of the Raman investigations has increased significantly. Moreover, the development of several new capabilities such as estimation of cellulose-crystallinity, ability to analyze changes in cellulose conformation at the local and molecular level, and examination of water-cellulose interactions have made this technique essential for research in the field of plant science. The FT-Raman method has also been applied to research studies in the arenas of biofuels and nanocelluloses. Moreover, the ability to investigate plant lignins has been further refined with the availability of near-IR Raman. In this paper, a review is provided that is focused on applications of 1064-nm FT Raman to these areas of research. It is hoped that the review will motivate the research community in the plant biomass field to adapt this technique to investigate their specific research needs.